(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Cancer remains one of the leading causes of death worldwide, with conventional drug discovery methods proving time-consuming, costly, and often ineffective in tackling the complexity and heterogeneity of malignancies. Objective: This review aims to explore the transformative role of artificial intelligence (AI), particularly machine learning (ML) and deep learning (DL), in accelerating and refining anti-cancer drug discovery. Methods: The article examines how AI is integrated into various stages of the drug development pipeline, including target identification, virtual screening, structure prediction, and clinical trial design. Emphasis is placed on synergizing AI with natural product-based drug discovery and addressing key computational, ethical, and regulatory challenges. Findings: AI has significantly improved the prediction of molecular properties, reduced attrition rates, and enabled the repurposing of existing drugs for new cancer indications. Virtual screening of phytochemicals and AI-aided solubility predictions are streamlining the path from lab to clinic. Attention mechanisms and transformer models are enhancing interpretability, while AI is optimizing clinical trials and enabling personalized medicine approaches. Conclusion: Artificial intelligence is revolutionizing cancer therapeutics by enabling faster, cost-effective, and personalized drug development. However, integration into routine practice requires addressing data quality, model interpretability, and ethical concerns. Continued interdisciplinary collaboration will be vital to fully harness AI’s potential in oncology drug discovery.